Catalytic properties of carbon xerogels for wet oxidation of aniline - Machado, Bruno (2010)
The main objective of this work was to develop carbon materials suitable to be used efficiently in catalytic wet air oxidation (CWAO) processes. Accordingly, carbon xerogels with different mesoporous surface area and chemistry were prepared by the conventional sol-gel approach and tested in the CWAO of aniline at 200ºC and 6.9 bar of oxygen partial pressure. The developed materials showed high activity in aniline and total organic carbon removal, a clear increase in the removal efficiency relatively to non-CWAO being observed. At 200ºC, almost complete aniline conversions were obtained after one hour oxidation with high selectivity to non-organic compounds. The materials were characterized by thermogravimetric analysis, N2 adsorption and scanning electron microscopy, in order to relate their efficiency to the chemical and textural characteristics. It was concluded that the removal efficiency increases with the mesoporous character of the materials and with the concentration of oxygen containing functional groups at their surface. The results obtained indicate that mesoporous carbon xerogels are promising catalysts for CWAO processes.